Karyotype evolution in Aeshna (Aeshnidae, Odonata) - Mola, L.M. (1994)
The haploid DNA content of Aeshna confusa (2n = 27, n = 13 + XO, male). A. bonariensis (2n = 26, n = 12 + neo-XY, male) and A. cornigera planaltica (2n = 16, n = 7 + neo-XY, male) has been determined (2.16 ± 0.16 pg, 1.81 ± 0.17 pg, and 2.08 ± 0.08 pg, respectively). Despite the differences in chromosome size and number, differences in DNA content between species are not significant. The karyotypic analysis of Aeshna species leads to the conclusion that fusions between autosomes or autosome and the sex chromosome, are the only chromosome rearrangement that occurred during evolution. In the species here studied, fusions have taken place with a minimal loss of DNA; however, other species of the genus show important differences in genome size, which cannot only be justified by fusion events.